Current Credit Risk Management Pr4actices in Chinese Banking Industry - Zheng, Hao (2008)
Bank loans can be characterized as the engine of the Chinese economy as the economy is almost financed by bank loans. As a result, Credit risk management in Chinese banks is not only the issue to those banks, but it is also essential to the stability of the whole economy. Inadequate credit risk management practices can create an unforeseeable disaster to China in the future, especially with a significant increase in credit expansion. In the last decade, the government has tried hard to reform the banking industry, but there are still problems in the banking industry. It is not surprise there are still problems in relate to credit risk management. The Basel committee (1999) defines bank credit risk as the potential that a bank borrower or counterparty will fail to meet its obligations in accordance with agreed terms. The goal of credit risk management is to maximise a bankÃÂ¢ÃÂÃÂs risk adjusted rate of return by maintaining credit risk exposure within acceptable level. In the context of asymmetrical information, the most effective way is to reduce asymmetry information between lenders and borrowers. This study will mainly follow this framework to carry out the study with some other considerations as well (loan pricing, credit risk models et al). The original objective of this study is to investigate the current credit risk management practices of loans to SMEs in China. However, the major results of this 1 study provide much wider findings. During the research, the researcher has discovered the problems that presented in SMEs loan also represent the general problem in credit risk management practices in Chinese Banks. Hence, after careful consideration, the aim of this study will be more likely to focus on the current credit risk management in Chinese banking industry. Key word: Credit risk management, asymmetric information, expert system, credit risk models, relationship banking and loan pricing models.